Legal Responsibility of Doctors in Determining Working Capacity Based on the Results of Worker Health Examinations - Rosmawati; Nasser; Agus, Tri (Institute for Law and Economics Studies, 2025)
One important part of occupational safety and health protection efforts is health examinations for workers. In this process, doctors play a central role in determining whether a worker is medically fit to perform their job duties. This decision on fitness for work is not only medical in nature, but also has significant legal implications for workers, employers, and doctors themselves. This study aims to examine the legal responsibilities of doctors in determining work fitness based on the results of medical examinations, as well as to explore the limitations and professional obligations of doctors in the context of employment. The research method used is normative juridical with a regulatory and literature study approach. The results of the study show that doctors are required to prioritize the principles of prudence, professionalism, and objectivity in providing medical assessments of work fitness. Errors or negligence in providing recommendations can lead to legal liability, whether civil, criminal, or medical ethics. Therefore, it is important for doctors to understand the legal basis, professional standards, and medical ethics in carrying out occupational health examinations